2011
DOI: 10.1166/jnn.2011.3787
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fe/MgO Catalyst Support Precursors for the Chemical Vapour Deposition Growth of Carbon Nanotubes

Abstract: Carbon nanotubes have been grown by the catalytic chemical vapour deposition (CCVD) method using an Fe catalyst supported on MgO. The influence of using either pure MgO or Mg(NO3)2 x 6H2O as the source of the MgO catalyst support as well as the effects of varying the Fe metal loading on the support has been investigated. The catalyst was prepared at room temperature by the wet impregnation method from a mixture of Fe2(SO4)3 x xH2O and either MgO or Mg(NO3)2 x 6H2O in aqueous solution; the weight percent of Fe/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…with Au. 80 Concerning the carbon source, the most preferred in CVD are hydrocarbons such as methane, 81 ethane, 82 ethylene, 83 acetylene, 84 xylene, 85,86 eventually their mixture, 87 isobutane 88 or ethanol. 89,90 In the case of gaseous carbon source, the CNTs growth efficiency strongly depends on the reactivity and concentration of gas phase intermediates produced together with reactive species and free radicals as a result of hydrocarbon decomposition.…”
Section: Chemical Vapour Depositionmentioning
confidence: 99%
“…with Au. 80 Concerning the carbon source, the most preferred in CVD are hydrocarbons such as methane, 81 ethane, 82 ethylene, 83 acetylene, 84 xylene, 85,86 eventually their mixture, 87 isobutane 88 or ethanol. 89,90 In the case of gaseous carbon source, the CNTs growth efficiency strongly depends on the reactivity and concentration of gas phase intermediates produced together with reactive species and free radicals as a result of hydrocarbon decomposition.…”
Section: Chemical Vapour Depositionmentioning
confidence: 99%
“…The chemical reaction mechanism contains two stages, including adsorption of CH 4 molecules on the surface of the carbon particles, followed by the decomposition of adsorbed CH 4 into H 2 and carbon. Therefore, it was Brought to you by | Rutgers University Authenticated Download Date | 10/5/15 11:26 AM concluded that the use of MgO increased the yield of synthesized nanocarbon compared to other support materials, including Al 2 O 3 and SiO 2 (Palizdar et al 2011, Su et al 2011, Jin et al 2012, Wang et al 2012a.…”
Section: Mgo Support Catalyst In Cnt Synthesismentioning
confidence: 99%
“…Ferrocene has been shown to be a good precursor of iron nanoparticles suitable to catalyze CNT growth [16][17]. Conventionally hydrocarbons such as methane, ethane, ethylene, acetylene, xylene and ethanol were used as a carbon source for the synthesis of CNTs [18][19][20][21][22][23]. The number of studies utilizing low-cost carbon sources for the synthesis of CNTs such as botanical hydrocarbon is very limited [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%